Surface behavior of sphingomyelins with very long chain polyunsaturated fatty acids and effects of their conversion to ceramides - Peñalva, Daniel Alejandro (2014)
Molecular species of sphingomyelin (SM) with nonhydroxy (n) and 2-hydroxy (h) verylong-chain polyunsaturated fatty acids (n- and h-28:4, 30:5 and 32:5) abound in rat spermatogenic cells and spermatozoa. These SMs are located on the sperm head,where they are converted into the corresponding ceramides (Cer) after completion of the acrosomal reaction, as induced in vitro. The aim of this study was to look into the surface properties of these unique SM species and how these properties change by the SM→Cer conversion. After isolation by HPLC, these SMs were organized in Langmuir films and studied alone, in combination with different proportions of Cer, and during their conversion into Cer by sphingomyelinase. Compression isotherms for all six SMs under study were compatible with a liquid-expanded (LE) state and showed large molecular areas. Only the longest SMs (n-32:5 and h-32:5 SM) underwent a phase transition upon cooling. On the other hand, the abundant h-28:4 Cer exhibited an unusual highly compressible liquid-condensed (LC) phase, compatible with a high conformational freedom of Cer molecules but with the characteristic low diffusional properties of the LC phase. In mixed films of h-28:4 SM / h-28:4 Cer, the components showed a favourable mixing in the LE phase. The monolayer exhibited h-28:4 Cer-rich domains both in premixed films and when formed by the action of sphingomyelinase on pure h-28:4 SM films. In conclusion, while the SMs from sperm behaved in a way similar to shorter acylated SMs, the corresponding Cers showed atypical rheological properties that may be relevant for the membrane structural rearrangements that take place on the sperm head after completion of the acrosomal reaction.